Territorial Innovation Patterns in Romania. Future Pathways for Smart Specialization - Cristina Șerbănică (Transylvanian Review of Administrative Sciences, 2021)
This study examines the territorial patterns of innovation in Romania, a country labelled as ‘modest innovator’. Our main assumption is that the large heterogeneity in the sub-national innovation patterns is not captured in the typologies developed for the NUTS2 regions. Consequently, the study proposes a categorization of the Romanian NUTS3 counties according to their innovation performance and structural characteristics, by means of a two-step factor analysis combined with hierarchical cluster analysis. The results point to the existence of five territorial groupings with similar characteristics: knowledge-intensive hubs, technology-intensive platforms, diversified agglomerations, industrial production zones and structurally challenged regions. Taken together, the results suggest the need to prioritize structural transformation and embrace the broad-based innovation concept.